Pengaruh Citra Merek dan Harga Terhadap Keputusan Pembelian Hand Sanitizer Fitso di Jakarta - Maria Palentina; Donant Alananto Iskandar (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of brand image and price on purchasing decisions for Fitso hand sanitizers in Jakarta. The data collection method in this study used a questionnaire and a sample of 125 respondents in this study used a non-probability sampling method. The results of the partial test or T test show that the brand image and price on the purchase decision of Fitso's hand sanitizer are significant. This condition is indicated by the significant gain of each independent variable less than =5%. Simultaneous test results show that the effect is used as a research model together on the purchase decision of Fitso's hand sanitizer is significant. This is supported by the result of the calculated F value which is greater than the F table, which is 66,345>3.07,indicating that there is a relationship between these independent variables together with the decision to purchase Fitso's hand sanitizer.